Optimal Placement of Internet of Things Gateways in Modern Electric Vehicle Charging Communication Systems - Putri, Syarifah Muthia; Ashari, Mochamad; Endroyono, .; Suryoatmojo, Heri (Engineering, Technology & Applied Science Research, 2025)
This paper presents the use of the optimal placement and number of the Internet of Things (IoT) gateway method to support home Electric Vehicle (EV) charging scheduling within an IoT system. A research was conducted for two scenarios. In scenario 1, a single IoT gateway was placed, while in scenario 2, the optimal number of IoT gateways was placed. The evaluation method for both scenarios utilized random placement, Equally Distributed Placement (EDP), and Genetic Algorithm (GA) placement. The optimization result ensures that the Path Loss (PL) value in the communication system does not exceed the specified PL threshold. This research aims to minimize the IoT gateways while ensuring quality data transmission, specifically maintaining a data rate above 31.72 kbps and a throughput of 24 kbps. The results indicate that both the random placement and EDP require more than three IoT gateways. Meanwhile, the GA placement requires only three IoT gateways, making it a more cost-effective communication solution.